Who Still Gets Ligated? Reasons for Persistence of Surgical Ligation of the Patent Ductus Arteriosus Following Availability of Transcatheter Device Occlusion for Premature Neonates - Julia K. Hoffmann; Zahra Khazal; Wievineke Apers; Puneet Sharma; Constance G. Weismann; Kira Kaganov; Craig R. Wheeler; Michael Farias; Diego Porras; Philip Levy; Sarah U. Morton (Journal of Cardiovascular Development and Disease, 2024)
(1) Background: To identify reasons for the persistence of surgical ligation of the patent ductus arteriosus (PDA) in premature infants after the 2019 Food and Drug Administration (FDA) approval of transcatheter device closure; (2) Methods: We performed a 10-year (2014–2023) single-institution retrospective study of premature infants (<37 weeks) and compared clinical characteristics and neonatal morbidities between neonates that underwent surgical ligation before (epoch 1) and after (epoch 2) FDA approval of transcatheter closure; (3) Results: We identified 120 premature infants that underwent surgical ligation (n = 94 before, n = 26 after FDA approval). Unfavorable PDA morphology, active infection, and recent abdominal pathology were the most common reasons for surgical ligation over device occlusion in epoch 2. There were no differences in demographics, age at closure, or outcomes between infants who received surgical ligation in the two epochs; (4) Conclusions: Despite increasing trends for transcatheter PDA closure in premature infants, surgical ligation persists due to unfavorable ductal morphology, active infection, or abdominal pathology.